Serum heart-type fatty acid-binding protein decreases and soluble isoform of suppression of tumorigenicity 2 increases significantly by long-term physical activity. (June 2019) - Sponder, Michael; Lichtenauer, Michael; Wernly, Bernhard; Paar, Vera; Hoppe, Uta; Emich, Michael; Fritzer-Szekeres, Monika; Litschauer, Brigitte; Strametz-Juranek, Jeanette
The aim of this prospective study was to investigate the influence of long-term physical activity on biomarkers for myocyte ischemia (heart-type fatty acid-binding protein, H-FABP), matrix remodelling/vascular stress (soluble isoform of suppression of tumorigenicity 2, sST2) and inflammation (soluble urokinase-type plasminogen activator receptor, suPAR). In this prospective observational study 109 subjects were recruited, 98 completed the study. Subjects were asked to perform exercise within the calculated training pulse for 8 months. The performance gain was measured/quantified by bicycle stress tests at the beginning and end of the observation period. Twenty-seven subjects with a performance gain <2.9% were excluded. suPAR, H-FABP and sST2 were measured in serum at baseline and after 2, 4 and 8 months by ELISA. We found a significant decrease in H-FABP (1.86 (0.86) to 1.29 (0.98) ng/mL; p<0.01) and a significant increase in sST2 levels (6126 (2759) to 6919 (3720) pg/mL; p=0.045) during the observation period of 8 months while there was no remarkable change in suPAR levels. We interpret the activity-induced decrease in H-FABP as sign of lower subclinical myocardial ischemia and better perfusion, probably due to a more economic metabolization and electrolyte balance. The increase in sST2 might reflect physiological sports-induced vascular stress. As H-FABP and sST2 play an important role in the pathomechanism of ischemic cardiomyopathy (iCMP) further studies should investigate the influence of regular physical activity on these biomarkers in a population of patients with iCMP. Trial registration number: NCT02097199.